Review on skin burn along with its treatment - Barge, Mrudula; Bhujbal, Rutuja; Palange, Anushka; Naikwadi, Nishigandha (Asian Journal of Pharmaceutical Research and Development, 2024)
Burn care is a very important medical concern. A weakened physical barrier function of the skin can lead to an infection because it exposes the body to microbial invasion. The process of healing damage from burn injuries, endocrine system irregularities, and the onset of an elevated metabolism with subsequent nutrient delivery are all hampered by the increased excretion of water as well as nutrients. Additionally, the body produces additional oxidative stress when inflammation as well as free radical activities are initiated. These processes can be largely prevented by maintaining enough levels of antioxidants as well as minerals in the body. As more information from studies and clinical experience is gained, the treatment of patients with thermal damage becomes increasingly successful. Furthermore, burn injuries can present unique issues that require lifetime rehabilitation or late intervention. In addition to improving patient safety and assistance, research on treating burn wounds has led to advances that will continue to improve functional recovery. This article reviews recent advancements in the medical care of burn victims, with a focus on the physiological characteristics and management of burn wounds.